Legal Responsibility for Provision of Personal Protective Equipment for Health Workers in Handling the Covid-19 Pandemic - Welli Zulfikar; Ardiansah Ardiansah (Universitas Katolik Soegijapranata Semarang, 2022)
Abstract: Since the beginning of 2020, COVID-19 has become a global health problem. In Indonesia, the number of COVID-19 continues to grow, including among health workers. Unfortunately, many died while taking care of those infected by this disease. The central government and local governments are responsible for providing the health workers with health service facilities, including personal protective equipment (PPE), to care for those infected by COVID-19 to break the chain of transmission. At the beginning of the spread of this disease, the number of PPE was limited even though the health workers urgently needed the equipment so they wouldn't be infected/exposed. This article will discuss the government's legal responsibility for providing PPE for medical staff to deal with the COVID-19 Pandemic.Keywords: Legal responsibility, COVID-19, PPE.Abstrak: Sejak awal tahun 2020, COVID-19 telah menjadi masalah kesehatan global. Di Indonesia jumlah kasus terus bertambah, termasuk jumlah petugas kesehatan yang terpapar COVID-19. Banyak dari petugas pelayanan kesehatan yang meninggal dunia ketika membantu merawat pasien yang terpapar. Pemerintah pusat dan pemerintah daerah memiliki tanggung jawab untuk menyediakan fasilitas pelayanan kesehatan bagi tenaga kesehatan, termasuk alat pelindung diri (APD). Pada awal penyakit ini menyebar, jumlah APD sangat terbatas padahal pelayan kesehatan sangat membutuhkan perlengkapan ini agar tidak tertular/terpapar. Artikel ini akan membahas tanggung jawab hukum penyediaan APD bagi staf medis oleh Pemerintah untuk menangani Pandemi COVID-19.Kata kunci :Tanggungjawab hukum, COVID-19,Alat Pelindung Diri (APD).